Values and Choices in Television Discourse
XVI, 255 p.
Keywords: The high-pressured, fast-paced environment of television production leaves little time for producers to reflect on how the potentialities of texts and images will be interpreted outside of the immediate broadcast imperatives. This volume brings together the producers and analysts of television in a formal and productive way.